2014
DOI: 10.1094/pdis-09-13-0920-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report on the Increased Distribution of Pathotype 704 of Plasmopara halstedii in Hungary

Abstract: Downy mildew of sunflower caused by Plasmopara halstedii (Farlow) Berlese et de Toni is a devastating disease worldwide. The treatment of seeds with fungicides and the use of resistant cultivars are widely employed control measures against this oomycete. Effective protection, however, may be hindered by the high genetic variability of the pathogen. There are 14 pathotypes of P. halstedii in Europe and as many as six of these were identified in Hungary before 2010 (1,4). In 2010, a new race, 704, was isolated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the last years of the survey, four races, 70471, 71461, 70571 and 71571, were detected with high virulence complexity which overcome Pl 6 and even Pl 15 genes. Beside these results, new occurrences of races 704 and 714 have been reported from Hungary (Bán et al ., ,) as well as a recent prevalence of race 714 in France (Virányi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years of the survey, four races, 70471, 71461, 70571 and 71571, were detected with high virulence complexity which overcome Pl 6 and even Pl 15 genes. Beside these results, new occurrences of races 704 and 714 have been reported from Hungary (Bán et al ., ,) as well as a recent prevalence of race 714 in France (Virányi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2007 the global number of P. halstedii races reached 36 (Gulya, ), 24 of which were reported in North America, 20 in Europe, 10 in Africa, and 5 races in both South America and Asia. In the following years, new races were found in Europe; 721 and 731 that were discovered in Bulgaria during 2007/8 (Shindrova, ), race 704 (Bán et al ., ) and 714 (Bán et al ., ) in Hungary and race 774 in France (Gascuel et al ., ). Recently, Virányi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first high virulent pathotype (704) was isolated in 2010 by Rudolf et al [ 22 ] from two sunflower fields in Hungary. In the following years, our research team confirmed the increased distribution of pathotype 704 in the country [ 27 ] and the emergence of three new P. halstedii pathotypes, 714, 724, and 734 [ 13 , 14 , 28 ] (New records are separated from previously published records by bold isolate numbers in Table 3 .). Previously, pathotype 724 was only identified from Hungary, but according to our present results, it was also detected in Romanian samples in 2019.…”
Section: Discussionmentioning
confidence: 55%
“…With the increase in the cultivation area of sunflower production in the 2000s in Hungary, downy mildew became more widespread and has recently been considered as one of the most important pathogens of sunflowers. One of the reasons for the increased significance of the disease is the occurrence of new pathotypes in some regions in Europe (and in Hungary, too) after 2010 (Bán et al 2014a(Bán et al , b, 2018Trojanová et al 2018). Another reason may be the decreasing sensitivity of the P. halstedii strains to mefenoxam.…”
mentioning
confidence: 99%